Expressive Surfaces: The Case of the Designer Vagina. (December 2017) - Jones, Meredith
In this article I set out an argument that skins and screens, once distinctly different types of surface, are merging. I show how in contemporary highly mediatized worlds skins are required to be visually expressive while also noting a parallel movement whereby screens are becoming more affective. Using the 'designer vagina' – specifically labiaplasty – as a case study I show how ideal bodies exist simultaneously as screen and as skin, as image and as affect. In turn, I argue that two-dimensional images and three-dimensional 'real life' bodies are blending in ways that parallel skin–screen mergers.